Assessment of various land use systems on soil potassium fractions and soil properties under lesser Himalayas - SHAH, AANISA MANZOOR; NAZIR, SHAISTA; SHAH, TAJAMUL ISLAM; MIR, YASIR HANIF; WANI, FAHEEM; RAI, A.P. (Journal of Soil and Water Conservation, 2023)
The current study was performed to assess the distribution of different forms of soil potassium under different land uses of temperate lesser Himalayas. Surface samples (0-20 cm) were collected from different land uses of district Kupwara except for the horticultural land use from which both surface (0-20 cm) as well as sub-surface samples (20-40 cm) were taken. The results revealed that water soluble potassium ranged from 0.02 to 0.06 cmolc kg-1, available potassium from 0.09 - 0.44 cmolc kg-1 and exchangeable potassium from 0.07-0.34 cmolc kg-1. Non-exchangeable potassium was noted to vary from 1.54-4.22 cmolc kg-1, boiling nitrate extractable potassium from 1.63-4.66 cmolc kg-1 lattice potassium from 26.43- 37.71 cmolc kg-1 while that of total potassium was observed to range from 28.05 - 42.36 cmolc kg-1. The magnitude of determined potassium forms was noted to be highest for agriculture irrigated soils followed by pasture soils and lowest in wasteland soils. A significant and positive correlation was observed among different potassium fractions. These fractions were noted to be affected by different physico-chemical properties of the studied soils.